Rapid Learning and Long-Term Memory for Dangerous Humans in Ravens (Corvus corax) - Blum, C. R.; Fitch, W. Tecumseh; Bugnyar, T. (Frontiers in Psychology, 2020)
Like many predatory species, humans have pronounced individual differences in their interactions with potential prey: some humans pose a lethal threat while others may provide valuable resources. Recognizing individual humans would thus allow prey species to maximize potential rewards while ensuring survival. Previous studies on corvids showed they can recognize and remember individual humans. For instance, wild American crows produced alarm calls toward specifically masked humans up to 2.7 years after those humans had caught and ringed them while wearing that mask. However, individual behavior of the crows or the impact of social features on their responses, was hardly examined. Here, we studied predator learning and social effects on responses, using a similar method, in captive common ravens (Corvus corax). We investigated learning and the impact of key social components on individual reactions to artificial predators. Human experimenters wore two types of masks while walking past two raven aviaries. In four training trials, the “dangerous” mask was presented while carrying a dead raven, whereas the “neutral” mask was presented empty-handed. Between every training trial and in all following trials, we presented both masks without dead ravens. We assessed the subjects’ (i) learning speed, (ii) selective long-term response, and (iii) potential effects of social dynamics on individual alarm calling frequency. Ravens learned quickly (often based on the first trial), and some individuals distinguished the dangerous from the neutral mask for the next 4 years. Despite having received the same amount and quality of exposure to the dangerous mask, we found pronounced individual differences in alarm calling that were fairly consistent across test trials in socially stable situations: dominance, but not sex explained individual differences in alarm responses, indicating the potential use of alarm calls as “status symbols.” These findings fit to those in wild bird populations and dominant individuals signaling their quality. Changes in the individuals’ participation and intensity of alarm calling coincided with changes in group composition and pair formation, further supporting the role of social context on ravens’ alarm calling.